Identification and Detection of Adulterated Camellia Oleifera Abel. Oils by Near Infrared Transmittance Spectroscopy. Issue 2 (1st February 2016) - Yuan, Jiao-Jiao; Wang, Cheng-Zhang; Chen, Hong-Xia; Ye, Jian-Zhong; Zhou, Hao
Abstract : Under the serious circumstances of Camellia oleifera adulteration, the accurate examination for quality trait of C. oleifera oil is extremely urgent. The use of near infrared transmittance spectroscopy as a rapid and cost-efficient classification technique for the authentication of Camellia oil was investigated. At the same time, the feasibility of near infrared transmittance spectroscopy for the rapid determination of soybean oil and maize oil adulterated in binary and ternary system Camellia oils was explored. The results showed that identifications was made based on the slight difference in raw near infrared transmittance spectra in Camellia oils, soybean oils, maize oils, and those adulterated with soybean and maize oil with discriminant equations techniques. Furthermore, the performance of near infrared transmittance spectroscopy models for binary and ternary system adulterated Camellia oils was satisfactory. Moreover, the near infrared transmittance spectroscopy calibration model of soybean oil (0–50%) in binary system adulterated Camellia oils was the best, and correlation coefficients of the cross-validation ( Rcv ) was 0.99999. For the near infrared transmittance spectroscopy calibration model of maize oil in binary system (0–50%) and ternary system (0–40%) adulterated Camellia oils, the Rcv were 0.99996 and 0.99961, respectively. In addition, the coefficients of external validation for three models were obtained (0.9998, 0.9999, and 0.9967, respectively). In all, near infrared transmittance spectroscopy could be conducted to identify Camellia oils and detect soybean oil and maize oil adulterated in binary and ternay system Camellia oils from the methodology.